Dynamics of component carbon fluxes in a semi‐arid Acacia woodland, central Australia. Issue 3 (29th August 2013) - Cleverly, James; Boulain, Nicolas; Villalobos‐Vega, Randol; Grant, Nicole; Faux, Ralph; Wood, Cameron; Cook, Peter G.; Yu, Qiang; Leigh, Andrea; Eamus, Derek
Abstract : [1] Vast areas in the interior of Australia are exposed to regular but infrequent periods of heavy rainfall, interspersed with long periods at high temperatures, but little is known of the carbon budget of these remote areas or how they respond to extreme precipitation. In this study, we applied three methods to partition net ecosystem photosynthesis into gross primary production (GPP) and ecosystem respiration (Re ) during two years of contrasting rainfall. The first year was wet (>250 mm above average rainfall), while little precipitation fell during the second year (>100 mm below average). During the first year of study, rates of GPP were large (793 g C m −2 yr −1 ) in this semi‐arid Mulga ( Acacia aneura ) and grass savanna due to complementary photosynthetic responses by the canopy and C4 understorey to cycles of heavy rainfall. Patterns in GPP during the summer and autumn matched those in leaf area index (LAI), photosynthetic activity, and autotrophic respiration. During the dry year, small but positive photosynthetic uptake by Mulga contributed to the neutral carbon budget (GPP / Re  = 1.06 ± 0.03). Small rates of photosynthesis by evergreen Mulga when dry were supported by storage of soil moisture above a relatively shallow hardpan. Little soil organic matter (1.1%) was available to support heterotrophic respiration (Rh ) without input of fresh substrate. The two largest sources of Re in this study were autotrophic respiration by the seasonal understorey and Rh through decomposition of fresh organic matter supplied by the senescent understorey. Key Points: Photosynthesis of C3 and C4 species was enhanced by heavy rainfall Soil moisture contributed to avoiding net carbon loss during drought Respiration was limited by substrate availability, moisture, LAI and GPP